Filsafat hukum :perspektif historis / Carl Joachim Friedrich; Penerjemah, Raisul Muttazien; Penyunting; Nurainun Mangunsong - FRIEDRICH, Carl Joachim (Empowerment of society institute, 2014)
xii, 365 hlm. ; 25 cm